A Causal Model of Neutralization Acceptance and Delinquency: Making the Case for an Individual Difference Model. (May 2014) - Topalli, Volkan; Higgins, George E.; Copes, Heith
Traditionally, neutralization theory has been conceptualized as a situational strategy employed by offenders to preemptively assuage the guilt they anticipate from contemplated offending and delinquency, and thereby promote offending. While scholars have established that neutralizing and delinquency are related, they have yet to sufficiently determine whether this relationship is causal in nature, or whether neutralizing should be thought of as an individual difference. In this study, we used trajectory analysis and structural equations modeling (SEM) techniques on GREAT (Gang Resistance Education and Training) data to find that juveniles coalesced into four stable and distinct neutralizing and delinquency groups. These trajectories were parallel across ages 12 to 16, and systematically related to each other (e.g., higher neutralizing trajectories with higher delinquency trajectories). Subsequent SEM analysis demonstrated a recursive, causal effect of neutralizations on delinquency. Our results suggest that practitioners develop measures to identify "high" versus "low" neutralizers, which may have ramifications for the offender management and counseling.